Politics and Theology in the Historical Works of Yitzhak Baer - Yiftach Ofek (Religions, 2022)
Of the individuals most commonly associated with the so-called “Jerusalem School” of historiography—the first- and second-generation of scholars of Jewish history that coalesced around the Hebrew University in the first years of its existence—Yitzhak (Fritz) Baer (1888–1980) was probably the least overtly political. Yet, a careful reading of his writings reveals a mind that was heavily engaged with the social and political affairs of the day. Like most members of the Jerusalem School, Baer saw his scholarship as a contribution to the Zionist project—an attempt to influence the character of the renascent Jewish society. Although he did not proclaim or publicize his views as loudly as others, he nonetheless weaved his political views into the fabric of his historical research. By reading his historical works against their immediate political context, we can therefore begin to piece together what amounts to an original and comprehensive worldview.